Do increased organic loading rates accelerate aerobic granulation in hypersaline environment?. Issue 6 (December 2022) - Tang, Rui; Han, Xushen; Jin, Yan; Yu, Jianguo
Abstract: It is a common sense that high organic loading rate (OLR) leads to the faster formation of aerobic granular sludge (AGS), while the effects of increased OLR on the direct development of salt-tolerant aerobic granular sludge (SAGS) in hypersaline wastewater is still unknown. In this study, four identical sequencing batch reactors (SBRs) were directly fed with 3% salinity wastewater and operated at different OLRs to cultivate SAGS. Granules firstly appeared on Day 10, 7, 5, and 8, and dominated on Day 23, 16, 10, and 13 in four SBRs operated under OLR of 2.4, 3.6, 4.8, and 7.2 kg COD/m 3 ·d, respectively. The former three granules matured on Day 29 (D50 of 550 µm), 25 (D50 of 639 µm), and 25 (D50 of 808 µm), respectively, while the loose and fluffy filamentous granules cultivated under the highest OLR failed to reach the traditional criterion of AGS. Overall, increased OLR could accelerate the formation of AGS that had larger sizes and lower microbial diversities. However, unlike salt-free wastewater, the appropriate OLR for rapid formation of compact AGS in hypersaline wastewater was only 3.6 kg COD/m 3 ·d, since the higher OLRs with higher hydraulic selection pressure led to the massive sludge loss and the formation of instable fluffy granules during granulation period. Bacterial community analysis revealed Corynebacterium, Marinobacterium, Paracoccus, Halomonas, and Vibrio were the main genera in four SBRs, in which Corynebacterium had certain abundance at all OLRs, and Vibrio and Paracoccus favored low OLR, while Halomonas and Marinobacterium dominated the SBRs with high OLRs. This study contributed to a better understanding of SAGS granulation under different OLR conditions in hypersaline wastewater. Graphical Abstract: ga1 Highlights: Granulation at different OLRs in hypersaline wastewater was first studied. Larger granules with lower microbial diversities formed at higher OLR. High OLR led to massive sludge loss and formation of instable filamentous granules. The appropriate OLR for rapid SAGS formation was 3.6 kg COD/m 3 ·d. Paracoccus favored low OLR, while Halomonas and Marinobacterium were opposite.